Survey of Livestock Counting and Tracking Methods - Sarwar, Farah; Pasang , Timotius; Griffin , Anthony; Saeed-Ur-Rehman (Nusantara Science and Technology Proceedings)
Conventional livestock counting methods are tedious, time-consuming, and labor-intensive for farmers, which makes counting an irregular task. This inability to constantly monitor stock numbers gives farm rustlers sufficient time to steal farm animals and hence leads to a significant financial loss annually. To overcome this issue, research using unmanned aerial vehicles (UAVs) in pastoral farming is growing progressively since the last decade, but their use is still limited to some extent. This research article gives a detailed analysis of the existing hardware-based and software-based methods. The impact of shifting from current methods to a UAV-based system is discussed using the findings of research articles, and algorithms for object detection in images and tracking in videos are also analyzed. The article concludes that there are still unexplored practical uses of UAV in pastoral farming for monitoring, counting, and tracking farm animals, especially in countries like New Zealand, where pastoral products cover a major portion of export revenue.